Functional characterization and expression profiling of glyoxalase III genes in date palm grown under abiotic stresses. Issue 2 (27th October 2020) - Jana, Gerry A.; Krishnamurthy, Pannaga; Kumar, Prakash P.; Yaish, Mahmoud W.
Abstract: Methylglyoxal (MG), a by‐product of various metabolic processes, including glycolysis, is a highly reactive cytotoxic metabolite. The level of MG in the cell is maintained at a non‐toxic level via MG detoxification pathways such as the universal glyoxalase system, including glyoxalase I/II/III enzymes. Glyoxalase III (DJ‐1) can breakdown MG to d ‐lactate in a single step without reducing glutathione (GSH). Elucidating the function of the DJ‐1 gene family may provide further knowledge about its role in plants under abiotic stresses. Here, we characterize four glyoxalase III genes ( PdDJ‐1B1, PdDJ‐1B2, PdDJ‐1C, and PdDJ‐1D ) encoding the conserved DJ‐1 domain in the genome of the date palm, a crop with high drought and salinity tolerance. The expression level of the PdDJ‐1 genes increased in date palm leaves upon salinity treatment. In addition, overexpression of PdDJ‐1 genes in Escherichia coli and the complementation in yeast hsp31Δ knockout mutant cells enhanced their growth rate and reduced the accumulation of reactive oxygen species (ROS) under MG and oxidative stress conditions as shown by the flow cytometry assay. Subcellular localization using confocal microscopy revealed the accumulation of PdDJ‐1B1, PdDJ‐1C, and PdDJ‐1D in the chloroplast, whereas PdDJ‐1B2 was localized to the cytosol. Remarkably, constitutive expression of the PdDJ‐1C gene in Arabidopsis thaliana Columbia (Col‐0) resulted in the generation of non‐viable albino plants implying that PdDJ‐1C plays a critical function in chloroplast development. These findings suggest that PdDJ‐1 protein has an important function in MG‐detoxification and maintaining the redox balance in date palm plants under abiotic stress conditions.